Morphometrics Reveals Complex and Heritable Apple Leaf Shapes - Migicovsky, Zoë; Li, Mao; Chitwood, Daniel H.; Myles, Sean (Frontiers in Plant Science, 2018)
Apple (Malus spp.) is a widely grown and valuable fruit crop. Leaf shape is important for flowering in apple and may also be early indicators for other agriculturally valuable traits. We examined 9,000 leaves from 869 unique apple accessions using linear measurements and comprehensive morphometric techniques. We identified allometric variation as the result of differing length-to-width aspect ratios between accessions and species of apple. The allometric variation was due to variation in the width of the leaf blade, not length. Aspect ratio was highly correlated with the primary axis of morphometric variation (PC1) quantified using elliptical Fourier descriptors (EFDs) and persistent homology (PH). While the primary source of variation was aspect ratio, subsequent PCs corresponded to complex shape variation not captured by linear measurements. After linking the morphometric information with over 122,000 genome-wide SNPs, we found high SNP heritability values even at later PCs, indicating that comprehensive morphometrics can capture complex, heritable phenotypes. Thus, techniques such as EFDs and PH are capturing heritable biological variation that would be missed using linear measurements alone.